The praying mantises of the Maltese Islands: distribution and ecology (Mantodea) - Cassar, Thomas (Fragmenta entomologica, 2020)
This study presents a species account of the mantises of the Maltese Islands, including notes on the ecology and distribution of each species. A total of three species are known to exist locally; Ameles spallanzania (Rossi, 1792), Mantis religiosa (Linnaeus, 1758) and Rivetina baetica Rambur, 1839. The presence of Ameles decolor (Charpentier, 1825) cannot be confirmed by any recently collected material, but the species is not excluded from the Maltese entomofauna. Two doubtful records are also discussed. All species present in the archipelago are typically found in Southern Europe and the Mediterranean basin.